Exploring pta alternatives in the development of ruthenium–arene anticancer compounds - Kljun, Jakob (2023)
Organoruthenium pyrithione (1-hydroxypyridine-2-thione) complexes have been shown in our recent studies to be a promising family of compounds for development of new anticancer drugs. The complex [(n⁶-p-cymene)Ru(pyrithionato)(pta)]PF₆ contains phosphine ligand pta (1,3,5- triaza-7-phosphaadamantane) as a functionality that improves the stability of the complex and its aqueous solubility. Here, we report our efforts to find pta alternatives and discover new structural elements to improve the biological properties of ruthenium anticancer drugs. The pta ligand was replaced by a selection of phosphine, phosphite, and arsine ligands to identify new functionalities, leading to improvement in inhibitory potency towards enzyme glutathione S-transferase. In addition, cytotoxicity in breast, bone, and colon cancers was investigated.